2010
DOI: 10.1139/w10-087
|View full text |Cite
|
Sign up to set email alerts
|

Passive protection of purified yolk immunoglobulin administered against Shiga toxin 1 in mouse models

Abstract: Shiga toxins produced by Escherichia coli O157:H7 cause a wide spectrum of enteric diseases, such as lethal hemorrhagic colitis and hemolytic uremic syndrome. In this study, the B subunit protein of Shiga toxin type 1 (Stx1) was produced in the E. coli system, was further purified by Ni-column Affinity Chromatography method, and was then used as an immunogen to immunize laying hens for yolk immunoglobulin (IgY) production. Titers of IgY increased gradually with boosting vaccination and, finally, reached a leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…18 Eighteen eggs for obtaining IgY were collected from 50 to 65 d after initial immunization. The yolks were separated, pooled and well mixed with 9 times volume of distilled water (pH 2.5-2.8).…”
Section: Hens Immunizationmentioning
confidence: 99%
“…18 Eighteen eggs for obtaining IgY were collected from 50 to 65 d after initial immunization. The yolks were separated, pooled and well mixed with 9 times volume of distilled water (pH 2.5-2.8).…”
Section: Hens Immunizationmentioning
confidence: 99%
“…Although a high antibody response was achieved at the beginning of immunization, ELISA results from chicken sera showed that levels of specific antibodies were not constantly maintained in the immunized birds, in contrast to the results of Pauly et al (2009). It is possible that conjugation of Stx2B with a carrier may be necessary (Marcato et al, 2005) although Wang et al (2010) obtained a high titer of specific antibodies against B subunit from Shiga toxin type 1 without conjugation to a carrier and the response remained constant over one year. This suggests a possible negative effect of B subunit from Shiga toxin type 2 in laying hens.…”
Section: Discussionmentioning
confidence: 89%
“…34,35) We also have reported that the toxins do not produce crossneutralizing antibodies in chickens. 15) Here, we found that rStx-1B and rStx-2B could induce cross-neutralizing antibodies, although their activity was low.…”
Section: Discussionmentioning
confidence: 90%